Inovasi Pembelajaran PAI Pra-KBM di SDN Banjarmlati 2 Kota Kediri Pasca Pandemi Covid-19 - Santani, Santani (Indonesian Proceedings and Annual Conference of Islamic Education (IPACIE), 2023)
The purpose of this research is to make Pre-KBM PAI Learning Innovations at SDN Banjarmlati 2, Kediri City. The research approach using descriptive qualitative was carried out with 3 (three) techniques of observation, interviews, and documentation. First, the first week of reading the Qur'an, Asmaul Husna and Dhuha prayers in congregation. In the second week, read the Koran or tadarus, read the poetry of Abu Nawas, and pray the duha sunnah in the congregation. In the third week, carrying out activities as usual, motivation and knowledge were given about the importance of keeping the Dhuha prayer and getting used to reading the poetry of Abu Nawas and Asmaul Husna. In the fourth week evaluate the activities that have been running. The results of the second study, reading prayers together in class after the clock sounded, taking ablution water, and lazily heading to the prayer room. Then read the Al-Qur'an together, Asmaul Husna, Abu Nawas poetry, and Duha prayer in congregation and end with congregational prayer. Third Research, the evaluation conducted at SDN Banjarmlati 2 related to pre-KBM PAI learning innovations is as follows: The teacher sees students showing their achievements in class, the teacher collects all the documents produced by students during the learning process such as written tests and oral tests.